Measurement of the non-prompt D-meson fraction as a function of multiplicity in proton-proton collisions at √s=13 TeV - Acharya, Shreyasi; Angelov, Venelin; Berdnikova, Anastasia; Bergmann, Luisa; Bórquez Cárcamo, Andrés G.; Crkovská, Jana; Danisch, Meike; Feuillard, Victor; Fokin, Ilya D.; Glässel, Peter; Kroesen, Martin; López, Jorge; et al. (Journal of high energy physics, 2023)
The fractions of non-prompt (i.e. originating from beauty-hadron decays) D0 and D+ mesons with respect to the inclusive yield are measured as a function of the charged-particle multiplicity in proton-proton collisions at a centre-of-mass energy of $$ \sqrt{s} $$= 13 TeV with the ALICE detector at the LHC. The results are reported in intervals of transverse momentum (pT) and integrated in the range 1 < pT < 24 GeV/c. The fraction of non-prompt D0 and D+ mesons is found to increase slightly as a function of pT in all the measured multiplicity intervals, while no significant dependence on the charged-particle multiplicity is observed. In order to investigate the production and hadronisation mechanisms of charm and beauty quarks, the results are compared to PYTHIA 8 as well as EPOS 3 and EPOS 4 Monte Carlo simulations, and to calculations based on the colour glass condensate including three-pomeron fusion.
Veröffentlicht: 16. Oktober 2023
*The ALICE collaboration: S. Acharya, V. Anguelov, A. Berdnikova, L. Bergmann, A.G. Borquez Carcamo, J. Crkovská, M.C. Danisch, V.J.G. Feuillard, I. Fokin, P. Glässel, M. Kroesen, J.A. López, A. Nath, Y. Pachmayer, K. Reygers, R. Schicker, A. Schmah, G. Skorodumovs, J. Stachel, S.F. Stiefelmaier, C.A. Van Veen, M.A. Völkl, B. Windelband, Y. Yuncu, F. Zanone [und sehr viele weitere Personen]
Gesehen am 16.05.2024
Im Titel steht der Buchstabe s unter dem Wurzelsymbol